REVITALISASI ILMU ‘ARUDHL DALAM PENDIDIKAN PESANTREN DI INDONESIA; KAJIAN ATAS MEMUDARNYA TRADISI KEILMUAN SANTRI - Al-MasduQi, Himayatu Syarafatil Furqon; Masrohatin, Siti (Mozaic: Islamic Studies Journal, 2024)
This paper discusses the science of 'Arudhl, studied by santri (students) in college (Islamic boarding schools). 'Arudhl is a branch of knowledge in Arabic literature, essential for understanding the beauty and rules of Arabic poetry. This discipline was developed by al-Imam al-Khalil bin Ahmad al-Farahidi to measure the accuracy of patterns and rhythms in Arabic poetry. During its golden age, 'Arudhl was highly valued as a tool to preserve the structure and elegance of classical Arabic poetry (sya’ir). The article examines the decline of 'Arudhl teaching traditions in Indonesian pesantren. Its primary focus is on the factors contributing to the decreased interest and ability to teach 'Arudhl, including changes in pesantren curricula, declining interest among santri in classical sciences, and the dwindling number of teachers proficient in this field. Furthermore, the article explores revitalization efforts to revive the teaching of 'Arudhl, such as designing balanced curricula, employing creative teaching methods, and improving teacher quality. By understanding the significance of 'Arudhl, this paper aims to encourage readers to appreciate the richness of Arabic literary traditions and their role in shaping a strong cultural identity.